Housing Market Access in the Lisbon Metropolitan Area: Between the Financial and the Pandemic Crises - Gonçalo Antunes; João Seixas (Critical Housing Analysis)
The Portuguese housing market underwent major transformations between 2010 and 2020. Until then, a delicate but resentful stability had long existed, with distorted rent schemes and low annual price increases proportional to the national economy and the income of the Portuguese population. After the financial crisis, several internal and external variables converged to dramatically change this scenario. In recent years, a growing number of researchers have centred their attention on the difficulties that the Portuguese urban middle-class populations are facing in trying to find homes. This paper analyses these challenges and their impact quantitatively, focusing on the affordability of housing for purchase or rent and considering synthetic indicators for average household incomes in the Lisbon Metropolitan Area between the beginning of 2016 and the end of 2019. The results show that the cost of buying or renting a house in the main Portuguese urban system has become much more detached from local incomes. The article concludes with reflections on the structural reasons for the enduring inequalities in the housing markets and the difficulties recognising territorial cohesion and spatial justice as important elements shaping urban and housing policies in Portugal.